Canada’s economic centre of gravity: New estimates using local labour market areas - Lee, Annie; Breau, Sébastien (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2024)
This paper provides new estimates of Canada’s economic centre of gravity using self-contained labour market areas as the regional unit of analysis. We find that from 1986 to 2019, Canada’s economic centre of gravity shifted from east to west by a net distance of 173 km, or approximately 3.1% of the distance separating Canada’s most easterly point (Cape Spear, Newfoundland and Labrador) and the Yukon-Alaska border in the northwest. Within this overall westward shift, we identify five distinct movement vectors where major directional changes have taken place driven in large part by fluctuating prices in resource- (particularly energy-) based commodity prices.